Comunicação e percepção no ciberespaço: um estudo sobre a experiência de imersão em ambientes lúdicos interativos - Lopes, Cláudia Ribeiro Monteiro (2013)
This Doctoral Research deals with the relationships between communication and perception in cyberspace. The scope of this investigation encompasses the immersive experience of the participants in games and the interaction of these participants with their virtual representations in the form of different spectres. For all theoretical purposes, the reception and resignificance of stimuli from the sensitive world by the subject of the sensation were apprehended through the concept of cyberspace, a typical and known phenomenon of cyberculture. Cyberculture, in turn, was understood as a socio-historical period marked by the dissemination of digital technologies and networks, and in its current state, by the overdetermination of the civilizing process through cyberspace. The research problem has to do with the peculiarities of the modus operandi of perception during immersion in online multiuser games and to their repercussions on the currently perceivable anthropological mutations in relation to the real world inherited from historical tradition. This research belongs to the field of studies about forms of social and cultural insertion of virtual technologies and networks, thus addressing an emerging theme in the area of Communication. The theoretical and epistemological foundations of this study include perspectives about perception (Maurice Merleau-Ponty, Paulo Sérgio do Carmo and Lucia Santaella), cyberperception (Roy Ascott, Lucia Leão and Santaella), cyberculture (Eugênio Trivinho), the body (Merleau-Ponty, Santaella and Trivinho), interactive immersion (Derrick de Kerckhove and Trivinho) and games (Joan Huiguinza, Tom Bissel, Jane McGonigal and Arlindo Machado). In view of the nature of this Doctoral Research, the methodology encompasses bibliographic research and review and corpus analysis, consisting of online games, whose scenes and narratives will be taken as media immersion environments for previously selected players. With these characteristics, situated in the line of research Mediatic Culture and Environments of the Program of Postgraduate Studies in Communication and Semiotics of PUC/SP (PEPGCOS/PUC-SP), the objectives of this investigation are (a) grasp the specificity of the esthetic and perceptual experience online, in the ambit of the Abstract games; (b) verify the possible implications of cyberspace in the player s ordinary (offline) life; and (c) contribute to the development of studies in this thematic field